Robot-assisted donor nephrectomy: Initial results and comparison with the hand-assisted laparoscopic technique. A retrospective study. (June 2022) - Idu, Mirza M.; Bemelman, Frederike; Nurmohamed, Azam; van der Pant, Karlijn
Abstract: Background: The aim of this study is to evaluate feasibility and safety of robotic-assisted donor nephrectomy (RADN) as compared with the hand-assisted laparoscopic technique (HALDN). Patient and methods: This is a retrospective study of the first 83 consecutive RADN procedures which were compared with a group of 103 consecutive HALDN procedures. Results: The median operating time in the RADN group and the HALDN group were respectively 173 (SD = 37) and 137 (SD = 29) min (p = 0.000). The mean first warm ischemia time (min, SD) in the RADN and HALDN group were respectively 2.60 (0.78) and 2.15 (0.38) (p = 0.000). The median blood loss (ml, SD) in the RADN and HALDN group were respectively 33 (87) and 64 (146) ml (p = 0.000). There were no statistically significant differences in post-operative pain-score, post-operative length of stay and complications between the two groups. There were also no statistically significant differences in recipient serum creatinine at 1 week and 1 month after transplantation. The median recipients eGFR (CKD-EPI) at 1 week in the RADN and HALDN group were respectively 50 (SD = 20) and 38 (SD = 19) (p = 0.018) and at 1 month respectively 52 (SD = 16) and 47 (SD = 15) ml/min/1.73m2 (p = 0.090). Conclusion: Robotic-assisted donor nephrectomy is an evolving technique which is safe for the donor and for the graft. Highligts: Robotic-assisted donor nephrectomy (RADN) is safe for the donor and for the graft. RADN have a longer operation time than laparoscopic donor nephrectomy (HALDN). RADN have longer warm ischemia time, but less blood loss compared with HALDN. No differences in pain, complications, hospital stay and graft function.